Resource Allocation Algorithm of Cloud Computing Infrastructure Services based on Continuous Optimization Algorithm - Lu, Wenyi (IOP conference series. Materials Science and Engineering, 2020)
The cloud environment is extremely complex, dynamic and changeable. How to use cloud services efficiently to create economic benefits for enterprises and even society is a matter that most scholars and manufacturers pay close attention to at present. Therefore, the resource allocation of cloud computing becomes the focus of research. The purpose of this paper is to further study the resource allocation algorithm of cloud computing infrastructure services. Firstly, the IAAs mode in three main application modes of cloud computing is introduced in detail. Based on the understanding of optimization theory, the resource allocation algorithm of cloud computing infrastructure services with continuous optimization algorithm is established. The experimental results show that the number of iterations of the three algorithms is generally on the rise with the increase of the number of task nodes. In general, the number of iterations of ant colony algorithm is less than that of genetic algorithm, and the performance of continuous optimization algorithm is better than that of both, which shows that it can promote the overall efficiency of the algorithm.